2021
DOI: 10.1136/bmjopen-2020-042556
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to promote family member involvement in adult critical care settings: a systematic review

Abstract: ObjectiveTo identify, appraise and synthesise evidence of interventions designed to promote family member involvement in adult critical care units; and to develop a working typology of interventions for use by health professionals and family members.DesignMixed-method systematic review.Data sourcesBibliographic databases were searched without date restriction up to June 2019: MEDLINE, EMBASE and CINAHL; the Cochrane Central Register of Controlled Trials, Joanna Briggs and Cochrane Libraries. Back issues of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Consistent with previous studies, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] our results revealed that visitor behavior was frequently associated with a decreased risk of patient harm. For example, we found that visitor communication with staff was most frequently reported as decreasing risk of harm and was distributed across all seven event types.…”
Section: Implications Of Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] our results revealed that visitor behavior was frequently associated with a decreased risk of patient harm. For example, we found that visitor communication with staff was most frequently reported as decreasing risk of harm and was distributed across all seven event types.…”
Section: Implications Of Findingssupporting
confidence: 92%
“…Previous research has demonstrated the positive influence of visitors on patient outcomes. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] For example, studies have found that visitors can successfully participate in patient safety interventions, such as fall prevention 15,16 and rapid response activation. 9 The potential for visitors to contribute to an increased risk of patient harm is less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the family might not be able to support their patients during these critical moments. Recommendation has been made in this regard as future interventions, and family involvement decision is to be at different levels of different kinds based on family choice, readiness, and preparedness for that [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proactive family communication, enabling flexible visiting and bedside presence, as well as involvement in care and decision making particularly in terms of long‐term planning were actionable processes identified during our analyses. Family members are integral to ensuring the wishes of patients inform decision making (Azoulay et al, 2014) to patient's recovery (Xyrichis et al, 2021) but also need psychological support and care from the ICU team (Dale et al, 2020; Herridge et al, 2016). Importantly, in their ethnographic work, Rak and colleagues (Rak et al, 2020) found engaged family members was one of the characteristics associated with high performing Long‐Term Acute Care Hospital.…”
Section: Discussionmentioning
confidence: 99%